Critical failures. (April 2018) - Handman, Courtney
Critique in evangelical Christian contexts has usually been seen as a practice in service of finding the universal. However, I examine a number of contexts in which Christian critique seems to produce serial difference. I suggest that this seriality may itself be seen as a basis on which possibility and alternatives can be found, rather than just as serial failures to reach the universal. I briefly compare different events of serial transformations, in the United States as well as in Papua New Guinea, the site of my ethnographic research on denominational difference.